Structural behaviour of 2D post-tensioned precast beam-column sub-assemblages subjected to column loss scenario - Tran, Manh Ha (2023)
Many previous studies have investigated alternative load path (ALP) mechanisms of 2D reinforced concrete (RC) beam-column sub-assemblages under column removal scenarios. However, how precast and prestressed RC structures respond under a column loss scenario receives far less attention, as evident from a lack of published test data. Herein, five 2D post-tensioned precast RC sub-structures subjected to a middle column loss scenario were tested by multi-point quasi-static loading. In all the specimens, individual precast members such as beams and columns were joined together through wet connection. The study focused on investigating the combined effects of post-tensioned tendon (PT) and wet connection on load-resisting mechanisms and the influence of basic parameters such as unbonded and bonded PT, T-beam effect, and boundary conditions. The test results indicated that both unbonded and bonded parabolic-shaped PT significantly enhanced compressive arch action (CAA) and catenary action (CA) beyond basic flexural capacity, and also changed the plastic hinge mechanism in the precast beams. The specimen with unbonded PT could provide greater residual capacity than bonded PT, but the former was severely damaged by fracture of normal reinforcement and crushing of concrete rather than fracture of the tendon. In addition, the effects of T-beam and boundary conditions are discussed in detail. Finally, new design criteria for precast and post-tensioned concrete structures under column removal scenarios are proposed for structural engineers to take advantage of high-strength tendons and avoid failure at critical locations by precast joints.